EFFECT OF EXERCISE ON TRPV1 EXPRESSION IN THE MUSCLE OF GALUR WISTAR RATS - Hanna Goenawan; Raisa Zahra; Putri Teesa Radhiyanti; Julia Ramadhanti; Vita Murniati Tarawan; Fifi Veronica (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Exercise is an activity that induces acid generation as one of the TRPV1 stimulants. Activation of TRPV1, a pain receptor, by acid, can lead to the formation of neuropeptides such as substance P and calcitonin gene-related peptides as a cause of inflammation and pain. However, chronic TRPV1 activation triggered by exercise can cause TRPV1 desensitization. Objective: Aim of this study was to examine the effect of different intensity exercise on TRPV1 mRNA expression in gastrocnemius muscle. Methods: This study was experimental study using animals models. Rats aged 12-24 weeks were given exercise interventions, a treadmill protocol, 5 times a week (30 min/day) with low (10 m/s), moderate (20 m/s), and high (30 m/s) intensity for 8 weeks. After exercise period, gastrocnemius muscle were isolated and subjected for TRPV1 mRNA expression analysis using semi quantitative real time PCR. Results: There was no changes of TRPV1 mRNA gene expression in gastrocnemius after treatment of different intensity exercise (p =0.694). Conclusion: As the conclusion, 8 weeks different intensity of exercise did not alter TRPV1 expression in gastrocnemius.